Abnormal children of a 47,XYY father. - Stoll, C (1979)
Abnormal children of two 47,XYY men were studied. One of these men had 2 normal daughters and a child, 45,X/46,XY, with gonadal dysgenesis. The other man had 2 normal sons and a child with Down's syndrome. The extra chromosome 21 of this child came from the mother. Another 47,XYY man had 4 normal children.